Traffic Performance Analysis of Jalan Rahadi Usman and Jalan Khatulistiwa Concerning the Garuda Bridge Development Plan in Pontianak - Siagian, Rita Apriliyani; Said, Said; Sumiyattinah, Sumiyattinah (Fakultas Teknik Universitas Tanjungpura, 2025)
The separation between Pontianak Utara and Pontianak Kota Districts, previously connected via the Bardan